RANCANG BANGUN SISTEM INFORMASI BADAN EKSEKUTIF MAHASISWA UNIVERSITAS NEGERI PADANG BERBASIS WEB - Irwan Rusda; Legiman Slamet; Dedy Irfan (Universitas Negeri Padang, 2019)
Development of technology which progress rapidly has effect to change whole of aspects in human life. One of them is development of information technology. Development of information technologies can apply on web based information systems. Many agencies have moved to web based inforation systems because of web based is more efective and eficient used. BEM UNP as executive campuss organization has a budget which the aim is implement activities to bend students characters. Examples are national seminars, talkshow, debates, open recruitment for new members, etc. The activities definitely are not without process of registration from participants. Most of the students want to participate in that activity. Usually get troubles activity informations, or trouble in registration directly to committe web based information systems used is one of the effective facilities to share activities process. The design of web based information syste, of BEM UNP visualizes by UML with using several object oriented of visualized diagrams. The result of web based information systems of BEM UNP is web based informations systems which give informations to BEM UNP and to ease students who want to bem participants in activities are implemented by BEM UNP. Keywords: Information System, BEM UNP, CodeIgniter Framework.